Synchronization of Strategic Plan and Implementation in Legal Entity State University through Good University Governance - Prihatin, Eka (International Journal of Psychosocial Rehabilitation, 2020)
This article aimed to evaluate the health of institutions through the analysis of good university governance principles on legal entity state universities in Indonesia, which are granted their own autonomy in determining the management of their institutions to respond to the changes and challenges they face. The problem that occurs is how the analysis of GUG implementation which has several characteristics namely (1) openness; (2) participation; (3) legitimacy; (4) transparency; (5) effectiveness and efficiency; (6) accountability and availability;(7) predictability; (8) coherence; (9) services excellence in synchronizing the planning and implementation of the three principles of higher education (education, research, and community service) program namely Education, Research and Community Service effectively and efficiently. The methodology used was mixed methods, namely quantitative, qualitative and normative legal approaches, from 65 respondents, of 121 educational programs in planning stated 64.7% of respondents implemented, 22.94% of respondents stated they did not implement and the rest did not answer. 4 respondents answered 27 research programs showed that 89% were implemented and 11% stated they were not implemented. 4 respondents answered 20 community service programs showed that 72.5% were implemented and 27.5% were not implemented. Thus the synchronization between the strategic plan and the implementation of the three principles of higher education (education, research, and community service) in the category was quite good, it must be improved by (1) building appropriate policy communication; (2) building a model for selecting and establishing professional-based leaders; (3) discipline.